The role of some laboratory biochemical and blood tests for meningitis patients for early detection of the disease1 (مجلة البحوث الأكاديمية, 2020)
Meningitis is the inflammation of the membranes surrounding the brain and spinal cord, which is a gastrointestinal disease and complications of deafness, epilepsy and loss of concentration. The diagnostic methods of the disease are high temperature and stiffness of the neck and sensitivity of light and body convulsions and types of viral and bacterial meningitis. The study aimed to do some laboratory biochemical and blood tests for meningitis patients for early detection of the disease, the information was taken from the statistics and documentation department of Misurata Medical Center after approval from the center from 1 January2112 to 20 May 2019, the data were taken from patients' profiles such as age, gender, and type of meningitis as well as after medical analysis such as spinal fluid analysis and analysis of white blood cells and reactive protein c (CRP) in serum and culture CSF, the rate of entry to the period reached 5694 children, of which 46% were girls and 54% were boy and stay in center between 4 days and 13 years, the cases were diagnosed with medical tests and the number of infected cases reached 37 children, where the incidence of meningitis was 0.6% of the total number from the present study we find that some medical tests may play an important role in the detection of bacterial meningitis and this has been shown by several previous studies, especially the analysis of the reactive protein ( CRP) of the spinal fluid.
Keywords: Meningitis disease; Biochemical test; Blood test,; early detection